Pneumatic Insufflation to Confirm Distal Stoma When in Doubt - Saxena, Akshay Kumar; Subramanian, Pavithra; Bhatia, Anmol; Sodhi, Kushaljit Singh (Indian Journal of Radiology and Imaging, 2023)
Background Distal colostogram and ileostogram are commonly performed radiological procedures in the pediatric population. It is sometimes difficult to identify the distal stoma while performing these procedures.Aim The aim of this study was to describe a technique for the confident identification of distal stoma.Methods Injection of a small quantity of air through the catheterized stoma and following it can help to identify the stoma, as proximal or distal, based on anatomy of the delineated bowel.Conclusion Pneumatic insufflation is a simple, quick procedure to confidently identify the distal stoma whenever in doubt.
Keywords: colostogram; colostomy; distal stoma; ileostogram; ileostomy; pneumatic insufflation